Sequentially responsive biomimetic nanoparticles with optimal size in combination with checkpoint blockade for cascade synergetic treatment of breast cancer and lung metastasis. (October 2019) - Yu, Wenqi; He, Xueqin; Yang, Zhihang; Yang, Xiaotong; Xiao, Wei; Liu, Rui; Xie, Rou; Qin, Lin; Gao, Huile
Abstract: Recently, photodynamic therapy (PDT) emerges as a promising way to initiate immune response and being used in combination with chemotherapy. However, the antitumor effect is restricted due to the poor tumor penetration and retention, premature drug release and immunosuppressive environment of tumor sites. And as the size of nanoparticles plays a key role in drug delivery, series of hyaluronidase-responsive size-reducible biomimetic nanoparticles (mCAuNCs@HA) with different initial sizes are synthesized, and the optimal size of 150 nm is screened out because of the best blood circulation, tumor penetration and retention. Then the photosensitizer pheophorbide A and ROS-responsive paclitaxel dimer prodrug (PXTK) are co-loaded to facilitate on-demand drug release. The hydrolysis byproduct cinnamaldehyde in turn stimulates the ROS production by mitochondria, which compensates for the ROS consumed in the hydrolysis process. Anti-PD-L1 peptide (dPPA) is furthered loaded to alleviate the immunosuppressive environment of tumor and enhance the function of cytotoxic T lymphocytes activated by PDT-induced immunogenic cell death. The combination therapy activates CD4 +, CD8 + T cells and NK cells and enhances secretion of cytokines (TNF-α and IL-12) with tumor inhibition rate increased to 84.2% and no metastasis is observed, providing a viable combination therapy for better anti-tumor and anti-metastasis efficacy. Graphical abstract: Image 1